Empirical insights on understanding stakeholder influence - Susnienė, Dalia; Purvinis, Ojaras (Journal of Business Economics and Management, 2015)
The paper deals with the stakeholder management especially giving focus on the organization’s and stakeholder relationships issues. The purpose of the paper is to construct a new methodological approach by developing fuzzy logic model based on experts’ knowledge for conceptual insights on possible solutions for measuring stakeholders’ influence. The objective of the research includes identification of possible organization stakeholder interactions considering stakeholders’ influence according to such attributes/ factors as interest, power, benevolence, and reliability. The results reveal that fuzzy logic technique is a reliable and valid tool for modelling and visualizing knowledge about stakeholders’ influence on the organization. Finally, the results were tested on the real business data concerning stakeholders’ influence. A contribution of this paper is the application of fuzzy logic model to evaluate and/or predict stakeholders’ influence to the issues the organization seeks to solve and to provide relevant information for the stakeholder relationships management. First published online: 02 Oct 2013